2019
DOI: 10.3390/wevj10010002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Temperature on Electric Vehicles’ Energy Consumption and Range: Model Definition and Sensitivity Analysis Based on Nissan Leaf Data

Abstract: In this paper, a general quasi-steady backward-looking model for energy consumption estimation of electric vehicles is presented. The model is based on a literature review of existing approaches and was set up using publicly available data for Nissan Leaf. The model has been used to assess the effect of ambient temperature on energy consumption and range, considering various reference driving cycles. The results are supported and validated using data available from an experimental campaign where the Nissan Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…During the summer, smaller energy consumption was observed, 17% for urban conditions and 22% for rural residents, including braking energy recovery. The result of another investigation [56] shows decrease of possible driving range from 150 km at 20°C to 85 km at 0°C. Doyle A. et al, 2019 [57] indicated that interior thermal comfort systems consume an average of 14% of the total trip's energy by the cooling system and 18% by a heating operation.…”
Section: Discussionmentioning
confidence: 92%
“…During the summer, smaller energy consumption was observed, 17% for urban conditions and 22% for rural residents, including braking energy recovery. The result of another investigation [56] shows decrease of possible driving range from 150 km at 20°C to 85 km at 0°C. Doyle A. et al, 2019 [57] indicated that interior thermal comfort systems consume an average of 14% of the total trip's energy by the cooling system and 18% by a heating operation.…”
Section: Discussionmentioning
confidence: 92%
“…Under different simulation conditions, the cooling load in summer will cause a 17.2-37.1% range reduction, and in winter the heating load will cause a range reduction of 17.1-54.0% [34]. The effect of the HVAC system on EV's range, in the condition of variable ambient temperature, was investigated in the case of a Nissan Leaf [35]. Using experimental data, the authors conducted simulations for different driving cycles (NEDC-New European Driving Cycle, FUDS-Federal Urban Driving Schedule and SFUDS-Simplified Federal Urban Driving Schedule) considering extra urban, rural, and motorway driving profiles.…”
Section: Environmentmentioning
confidence: 99%
“…The energy consumption for the electric vehicles is influenced by the atmospheric conditions, not only from the point of view of the direct influence on the storage capacity of the batteries, but also from the point of view of the increase of the energy consumption due to the supply of the auxiliary systems (heating, ventilation, and air-conditioning in the vehicle), as demonstrated by Iora et al, in [18].…”
Section: Introductionmentioning
confidence: 99%